Algebra

How to solve d(d^-2)^-9? Please show and explain step-by-step.

  1. 👍 0
  2. 👎 0
  3. 👁 97
  1. What do you have to solve exactly? Do you by chance mean simplify?

    Should there be an equal sign in the expression that you typed?

    1. 👍 0
    2. 👎 0
    posted by Leo
  2. Simplify, sorry. The answer says d^19, but I don't get how.

    1. 👍 0
    2. 👎 0
  3. d^1 * d^(-2*-9)

    = d^1 * d^+18

    = d^19

    1. 👍 0
    2. 👎 0
    posted by Damon
  4. Thanks. Another one:

    (z^8)^0 z^5

    1. 👍 0
    2. 👎 0
  5. ANYTHING AT ALL^0 = ONE
    so
    z^5

    1. 👍 0
    2. 👎 0
    posted by Damon

Respond to this Question

First Name

Your Response

Similar Questions

  1. Math 7 A

    Note: For questions 5 and 6, remember to show all of the steps that you use to solve the problem. Be sure to use the text box where the question mark (?) first appears to show your mathematical work. You can use the comments field

    asked by jesse on November 20, 2017
  2. math

    Consider the sequence of steps to solve the equation: 2(x − 4) + 6x = 9x − 10 Which step in solving this equation is justified by the Commutative Property of Addition? Given ⇒ 2(x − 4) + 6x = 9x − 10 Step 1 ⇒ 2x − 8

    asked by Anonymous on October 25, 2018
  3. Algebra help

    f(x)=x^3-4x^2-x+4 How do I find the x-intercept for this? This is from my book: step 1: 0=x^3-4x^2-x+4 step 2: 0=x^2(x-4)+(-1)(x-4) step 3: 0=(x^2-1)(x-4) I know how to solve once I get to step 3, but in step 2, I don't know what

    asked by Claure on June 16, 2009
  4. Math

    I need help solving the problem not the answer. (Multiple Choice) The steps below show the incomplete solution to find the value of x for the equation 7x + 8 − 3x = −6 + 10: Step 1: 7x + 8 − 3x = −6 + 10 Step 2: 7x + 8 −

    asked by Ryan on March 30, 2017
  5. math

    Consider the sequence of steps to solve the equation: 5(x - 3) = 7x 2 Step 1 ⇒ 10(x - 3) = 7x Step 2 ⇒ 10x - 30 = 7x Step 3 ⇒ 3x - 30 = 0 Step 4 ⇒ 3x = 30 Step 5 ⇒ x = 10 Identify the property of equality which yields

    asked by Valerie on October 22, 2019
  6. 7th grade math

    How would you solve the problem below using subsitution method? 7x - 2y = 5 x = y If you could explain and show this step by step, it would help a lot. How would you solve the problem below using combination method? 3x - 2y = 12

    asked by saranghae12 on April 9, 2012
  7. algebra 1

    can someone please help me solve the question and explain to me and also show me specifically what to do step by step??? Q: what is the standard form of Y-8=2(x+2)?

    asked by Catarina on November 9, 2013
  8. math

    can someone explain step by step to solve system equations and example ill show here 3x+4y=-2 x=-2y

    asked by sherri on January 13, 2009
  9. math

    An equation and the steps to solve it are shown below: 3x − one over two (8x − 2) = 4 Step 1: 3x − 4x + 1 = 4 Step 2: x + 1 = 4 Step 3: x + 1 − 1 = 4 − 1 Step 4: x = 3 Which step was the error made and why? Step 1,

    asked by oscar on September 4, 2015
  10. math

    An equation and the steps to solve it are shown below: 3x − one over two (8x − 2) = 4 Step 1: 3x − 4x + 1 = 4 Step 2: x + 1 = 4 Step 3: x + 1 − 1 = 4 − 1 Step 4: x = 3 Which step was the error made and why? Step 1,

    asked by oscar on September 4, 2015

More Similar Questions